Biological medicinal products: reference and biosimilar products – selected issues - Kobuszewski, Bartosz (Journal of Education, Health and Sport, 2021)
Biological therapies are being used in many chronic conditions. Development of biosimilar medicines gives chances for wider access to biological treatment. The aim of the review was to present legal regulations of the marketing authorisation of biological medicines in the context of biosimilars medicines. The article focuses on the legislation of the European Union, which was established on the beginning of the XXI century and is very complex and strict. In the first part of the article were described basic terms in this field, such as biological medicine, biosimilar medicine, reference medicine and generic medicie. It also shows differnces between biosimilar and generic medicines. Main difference concerns the manufacturing process, because of which biosimilar will never be identical to the reference medicine. Next part concentrates on the proces of registration of new biological medicines, especially in the area of medicines’ indications to use and controversies related to them. The last part presents issues of the safety monitoring of biological medicines on european level. The purpose of european law in that field is to guarantee every registred biologic therapy is safe for the patients.